Exploring the Integration of Coastal and Marine Areas into Sustainable Development Strategies: Lessons from Africa - Eric O. Odada (Advances in Aquaculture and Fisheries Management, 2023)
The coastal and marine environments of the African region are uniquely situated to support a variety of activities and to serve diverse human needs for food, transport, and recreation. The pressures from growing populations in coastal zones of Africa, expanding coastal tourism, intensified fisheries, and a large number of other economic activities pose an increasing threat, which jeopardize the quality of these coastal and marine environments. Large-scale destruction of some of Africa’s most valuable resources, the coastal forests and mangroves, the lagoons and coral reefs has caused serious degradation of the environment, thus affecting the life of the coastal inhabitants and the economic development of the countries of the African region. The Seychelles Island in the western Indian Ocean for example, was famous for its luxuriant forests and an incredible abundance of wildlife. But many reefs have been mined for coral for the purpose of construction. Mangrove forests on the granitic islands have been raised to the ground or drained and reclaimed. Severe erosion is as a result of this destruction. Many African countries are confronted with serious manpower problems, which are proving to be great impediments in the economic development, especially of their coastal and marine areas. In many cases, the most important cause underlying these problems is the lack of adequate training facilities for the type of manpower required. The teaching of marine science and marine technology in universities of the region is a recent development and in many of the universities, there are as yet no comprehensive study programmes covering the whole spectrum of marine science and technology at the undergraduate or postgraduate level. The situation in regard to research in marine science and technology is equally unsatisfactory. To implement sustainable development of coastal and marine resources of the African region, there is an urgent need to: (1) build human resources by undertaking short-term academic training to strengthen existing capabilities; (2) promote public awareness by producing educational materials on the ecological and socio-conomic contributions of the marine resources and the consequences of unsustainable exploitation (3) organise policy workshops, seminar and/or conferences involving relevant policy and law-makers to increase their understanding of and commitment to the sustainable use of the resources in their coastal and marine areas, and (4) implement integrated coastal zone management programmes by establishing case studies in pilot sites in selected countries of the African region. The object of this paper is to review background information on the present status and trends of coastal and ocean development in Africa, and on the existing capabilities in the region to implement sustainable development strategies. It is intended to lay out the framework and strategy to be used in the design of an integrated management of coastal and marine areas in the region.